Law without nations? : why constitutional government requires sovereign states - Rabkin, Jeremy A. (Princeton University Press, 2005)
What authority does international law really have for the United States? When and to what extent should the United States participate in the international legal system? This forcefully argued book by legal scholar Jeremy Rabkin provides an insightful new look at this important and much-debated question. Americans have long asked whether the United States should join forces with institutions such as the International Criminal Court and sign on to agreements like the Kyoto Protocol. Rabkin argues that the value of international agreements in such circumstances must be weighed against the threat.